An increased risk of non‐Hodgkin lymphoma and chronic lymphocytic leukemia in US patients with Merkel cell carcinoma versus Australian patients: A clinical clue to a different mechanism of pathogenesis?. (19th March 2015) - Bloom, Romi; Amber, Kyle T; Nouri, Keyvan
Abstract: The US and Queensland populations both demonstrate an increased risk of secondary malignancies following the diagnosis of Merkel cell carcinoma (MCC). A recent Queensland study failed to demonstrate a significantly increased risk of developing non‐Hodgkin lymphoma (NHL) or chronic lymphocytic leukaemia (CLL) in these patients. In contrast, using the US Surveillance, Epidemiology, and End Results database, we demonstrate there is an increased risk in CLL and NHL following the diagnosis of MCC in the USA. We hypothesise that this difference may be a result of a differing pathogenesis.